2018
DOI: 10.1002/tsm2.19
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking in healthy and surgically repaired human Achilles tendons at different knee angles-A validation using implanted tantalum beads

Abstract: The exact injury mechanism of Achilles tendinopathy remains unknown, but sliding of fascicles relative to each other during loading may be an important factor. This study validated the motion of ultrasound speckles against actual tendon movement using tantalum beads as reference markers. In addition, the effect of different knee joint angles (ie, muscle activation) on tendon tissue shear and displacement during a single heel rise was investigated. The 10 male participants had tantalum beads inserted in the ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 16 publications
2
28
0
1
Order By: Relevance
“…In addition, also Bogaerts et al recently reported that knee joint ankle did not have an effect on regional Achilles tendon tissue displacement patterns during isometric contractions as measured in the sagittal plane . In contrast, while Beyer et al also observed that displacement of the anterior region of the Achilles tendon remained almost similar between plantarflexion tasks performed in knee extended and flexed (100° flexion) postures, the posterior region experienced smaller displacement in the knee flexed posture resulting in greater relative motion within the Achilles tendon in the knee flexed posture . However, in the study by Beyer et al, the outcome may be affected by the fact that loading conditions greatly differed between the knee extended and flexed postures, whereas in the current study, a maximal isometric contraction was done in both joint postures.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, also Bogaerts et al recently reported that knee joint ankle did not have an effect on regional Achilles tendon tissue displacement patterns during isometric contractions as measured in the sagittal plane . In contrast, while Beyer et al also observed that displacement of the anterior region of the Achilles tendon remained almost similar between plantarflexion tasks performed in knee extended and flexed (100° flexion) postures, the posterior region experienced smaller displacement in the knee flexed posture resulting in greater relative motion within the Achilles tendon in the knee flexed posture . However, in the study by Beyer et al, the outcome may be affected by the fact that loading conditions greatly differed between the knee extended and flexed postures, whereas in the current study, a maximal isometric contraction was done in both joint postures.…”
Section: Discussionmentioning
confidence: 92%
“…Recent advances in dynamic ultrasound imaging and various speckle tracking algorithms permit the measurement of localized tendon tissue displacements within the Achilles tendon . With the help of ultrasound speckle tracking, several recent in vivo studies have revealed non‐uniform motion within the Achilles tendon during passive joint rotations, active muscle contractions, and during locomotion . These observations of non‐uniform tendon motion, thus far isolated to sagittal plane measurements (ie, antero‐posterior differences), are consistent with sliding between adjacent subtendons.…”
Section: Introductionmentioning
confidence: 83%
“…25 A custom Matlab script (Matlab R2016b, The MathWorks Inc, USA) using a cross-correlation algorithm was used to track the tendon insertions on patella and tibia. 26 Around 10-20 tracking nodes were placed on either apex patellar or tuberositas tibia and tracking was performed twice at each location. Tendon deformation was determined as the distance between the insertions and was then correlated with force measurements using a custom-made excel template to generate a force-deformation curve.…”
Section: Patellar Tendon Biomechanical Propertiesmentioning
confidence: 99%
“…A recent study on human Achilles tendons used STU to investigate intratendinous displacement following surgery for unilateral tendon rupture [21]. Implanted tantalum beads were used to follow displacement of tendon speckles, but this was not feasible in the present study.…”
Section: Discussionmentioning
confidence: 99%